Mixed-charge pseudo-zwitterionic copolymer brush as broad spectrum antibiofilm coating. (June 2021) - Wu, Yang; Raju, Cheerlavancha; Hou, Zheng; Si, Zhangyong; Xu, Chen; Pranantyo, Dicky; Marimuthu, Kalisvar; De, Partha Pratim; Ng, Oon Tek; Pethe, Kevin; Kang, En-Tang; Chan-Park, Mary B.
Abstract: Zwitterionic polymers are classical antifouling polymers but they require specialized monomers that have cationic and anionic charges integrated into a single monomer. Herein, we show that pseudo-zwitterionic copolymers synthesized from a mixture of 2 monomers each having a single opposite polarity has excellent antibiofilm efficacy. We have discovered a new mixed-charge copolymer brush (#1-A) synthesized from 2 oppositely charged monomers, the anionic SPM (3-Sulfopropyl methacrylate) and the cationic AMPTMA ((3-Acrylamidopropyl) trimethylammonium chloride), that achieves broad spectrum in vitro antibiofilm effect of greater than 99% reductions against all six Gram-positive and Gram-negative bacteria tested. In the murine subcutaneous wound catheter infection models, the #1-A has good long-term anti-biofilm efficacy against MRSA and Pseudomonas aeruginosa of 3.41 and 3.19 orders respectively, outperforming previous mixed-charge copolymer coatings. We discovered a new method to choose the cationic/anionic pair combination to form the best antibiofilm copolymer brush coating by exploiting the solution polymerization kinetics disparity between the cationic and anionic monomers. We also showed that #1-A is softer and has higher hydration than the classical zwitterionic polymer. This study shows the possibility of achieving potent antibiofilm efficacy by combining readily available opposite singly charged monomers.